Computer Simulation of Pouring Grains Using Stick-Slip Model - Muhammad Hasan (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2008)
We applied the Stick-Slip model to simulate pouring grains processes via Granular Dynamics Simulation. The dynamics mechanism and the structure formation of the 2D and 3D systems are investigated. The results show that the shape of the generated piles in the 2D and 3D systems are similar when observed superficially, but the detailed structure and the dynamic behaviour leading to that structure are very different.